Defining the MCID, PASS and SCB for Arthroscopic Hip Preservation Surgery at Minimum Five-Year Follow-up. Issue 7 (31st July 2020) - Nwachukwu, Benedict; Beck, Edward; Kunze, Kyle; Chahla, Jorge; Drager, Justin; Nho, Shane; Rasio, Jonathan
Objectives: Minimal clinically important difference (MCID), substantial clinical benefit (SCB) and patient acceptable symptomatic state (PASS) have gained prominence as important variables in the orthopedic outcomes literature. In hip preservation surgery, much attention has been given to defining early clinically significant outcome, however, it is unknown what represents meaningful patient reported outcome improvement in the medium to long-term. The purpose of the present study was to define MCID, PASS and SCB at a minimum five years after hip arthroscopy for femoroacetabular impingement syndrome (FAIS). Secondarily, we sought to evaluate the time dependent nature of MCID, PASS and SCB. Methods: Patients undergoing hip arthroscopy for FAIS between January 2012 and March 2014 were included. Clinical and demographic data were collected in an institutional hip preservation registry. MCID, PASS, and SCB were calculated for each outcome score at 1-, 2-, and 5- years. MCID was calculated using a distribution-based method while PASS and SCB were calculated using an anchor method. Results: Two hundred and eighty-three patients were included with an average age of 34.2+11.9 years. The one year, two year and five-year MCID scores were as follows respectively: HOS-ADL (8.8, 9.7, 10.2); HOS-SS (13.9, 14.3, 15.2); mHHS (6.9, 9.2, 11.4) and iHOT-12 (15.1, 13.9, 15.1). PASS scores were as follows: HOS-ADL (89.7, 88.2, 99.2); HOS-SS (72.2, 76.4, 80.9); mHHS (84.8, 83.3, 83.6) and iHOT-12 (69.1, 72.2, 74.3). SCB scores were as follows: HOS-ADL (89.7, 91.9, 94.6); HOS-SS (78.1, 77.9, 85.8); mHHS (86.9, 85.8, 94.4) and iHOT-12 (72.6, 76.8, 87.5). More patients achieved MCID, SCB and PASS at two-year follow-up than at one-year follow-up. However, 79.3% of the patients achieved MCID by 5 years. Conclusion: The greatest proportion of patients achieve clinically significant outcome improvement at two-year follow-up after arthroscopic treatment of FAIS. Improvements are maintained out to five-year follow-up although there is a slight decrease in the proportion of patients achieving clinical significance. Table 1. Frequency of patients achieving any MCID, PASS, or SCB threshold at 1, 2, and 5-years 1-year 2-year 5-year p-value Any MCID 233 (82.6%) 247 (87.3%) 224 (79.3%) 0.035 Any PASS 191 (67.6%) 211 (74.9%) 191 (67.5%) 0.114 Any SCB 176 (62.3%) 190 (67.2%) 160 (56.6%) 0.034